Absurd uciekającego bytu - Tokarz, Bożena (Przestrzenie Teorii, 2007)
At the onset of the 21 st century art and literature emerge as a consequence of two orders: the past, that is the 20th century, and the future, anticipated - by and large - on the basis of previous experiences. The artistic consciousness of the past century is determined by contradictions, such as empathy and distrust, reason and sensation, rationalism and metaphysics, the subject and the object, the whole and the fragment. Leaving out one element in any of such oppositional pairs either leads to frustration, or to dogmatism, while the acceptance of their simultaneity - results in the removal of permanent points of reference in the sphere in which humans, objects, phenomena and values exist. In the 20th century, the loss of faith and the hardships of the quest for one's own identity led to a situation marked by absurdity: it caused the escape of being. The body flees from the man, theatricality runs away tram the theater, literariness escapes letters, literary scholarship flies from literature. The lack of identity turns any being-bound quality into void - yet art, literature, culture and man continue to exist nonetheless, functioning by the principle of similarity and difference.